The Meaning and Dynamics of the Bugis To Lotang Marriage Tradition from the Perspective of Islamic Family Law - Anita Apriliani; Islamul Haq; Muhiddin Bakri; Muhammad Ali Rusdi; Aris (UIN Siber Syekh Nurjati Cirebon, 2026)
Marriage in Indonesia reflects a dynamic interaction between religious norms and living customary practices; however, studies on the Bugis To Lotang community tend to be descriptive and rarely examine its compatibility with Islamic family law. This study aims to analyze the meaning and practice of the To Lotang wedding tradition, explore its dynamic changes, and assess its conformity with Islamic legal principles. This research employs a qualitative design using ethnographic and socio-legal approaches, supported by a normative juridical perspective. Data were collected through observation, in-depth interviews with customary leaders (Uwa’), and documentation in Amparita Village, Sidenreng Rappang Regency. The findings reveal that the To Lotang wedding tradition consists of pre-wedding, wedding, and post-wedding stages that embody symbolic, social, and spiritual meanings, reflecting values such as siri’ (self-esteem), pacce (solidarity), and respect for ancestors. The tradition has undergone adaptive changes due to modernization, particularly in the simplification of stages, without altering its core values. From the perspective of Islamic family law, most practices can be categorized as ‘urf (custom) that is permissible as long as they do not contradict Sharia principles. However, the absence of explicit ijab kabul raises concerns regarding legal validity, necessitating the integration of the Islamic marriage contract. This study contributes to the development of Islamic family law by offering a contextual understanding of the interaction between customary practices and Islamic law. Keywords: Marriage; Bugis To Lotang; Islamic Family Law; 'Urf; Cultural Dynamics